CGIAR Platform for Big Data in Agriculture - Plan of Work and Budget 2019 - CGIAR Platform for Big Data in Agriculture (CGIAR Platform for Big Data in Agriculture, 2019)
2019 is a pivotal year for the CGIAR Platform for Big Data in Agriculture. The Platform has made significant investments in its first two years in helping CGIAR data resources to become more organized and FAIR (Findable, Accessible, Interoperable, Reusable), and this year we expect these to begin to bear fruit: well described datasets observing the CGIAR core metadata schema, shared in up-to-date open repositories across all CGIAR Centers, will enable the development of new cross- Center and cross-domain query, visualization and research capabilities for the System. These new data capabilities, coupled with digital innovation processes, will unlock new analytical approaches, and enable CGIAR to leverage big data to solve development problems.